Value of rice mill feed as a feedstuff for backgrounding heifers - F.K. Brazle; K.P. Coffey (Kansas Agricultural Experiment Station Research Reports, 1990)
Stocker heifers were fed diets of either 67% rice mill feed + 33 % dehydrated alfalfa pellets (RA) or a 67% grain sorghum + 33% dehydrated alfalfa pellets (GA). The RA heifers consumed more feed daily but gained slower (P<.05), resulting in poorer feed efficiency. RA heifers also had a lower percentage shrink (P<.05) during the first 2 1/2 hr of simulated trucking. Rice mill feed is a poor feedstuff for growing calves when included in rations at high levels.
Keywords: Cattlemen& #x27; s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; By-products; Rice mill feed; Backgrounding